2020
DOI: 10.1177/1524838020967348
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Formal Responses to Intimate Partner Violence and Women’s Resistance Processes: A Scoping Review

Abstract: Intimate partner violence (IPV) literature addresses the ways in which women oppose violent male partners through acts of “everyday resistance.” There is a limited understanding, however, of the relationship between women’s resistance and their formal help-seeking in the context of IPV. Our scoping review, which includes 74 articles published in English-language journals between 1994 and 2017, attempts to help fill this gap by developing systematic knowledge regarding the following research questions: (1) How … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Second, an integral analysis of help-seeking behavior follows ecological approximations. In this regard, the current research follows recent recommendations for IPV analysis, including a range of factors and the multidimensional nature of the phenomena ( Hammock et al, 2017 ; Herrero et al, 2020 ; Juarros-Basterretxea, Herrero, et al, 2022 ; Juarros-Basterretxea, Ocampo, et al, 2022 ; Osborn & Rajah, 2020 ). A third strength of the present study is its ability to advance research on the effect of perceived reportability on the potential selection of various sources of help, from more informal to more formal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, an integral analysis of help-seeking behavior follows ecological approximations. In this regard, the current research follows recent recommendations for IPV analysis, including a range of factors and the multidimensional nature of the phenomena ( Hammock et al, 2017 ; Herrero et al, 2020 ; Juarros-Basterretxea, Herrero, et al, 2022 ; Juarros-Basterretxea, Ocampo, et al, 2022 ; Osborn & Rajah, 2020 ). A third strength of the present study is its ability to advance research on the effect of perceived reportability on the potential selection of various sources of help, from more informal to more formal.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical literature seems to support this claim. Hanson et al (2019) (see also Cheng et al, 2020 ; Cho et al, 2023 ) found that women tend to choose the police as help purveyors in more severe cases of IPV, suggesting that seeking help from the police reflects the desperation of the situation ( Osborn & Rajah, 2020 ). This finding leads to the following question: “Why do most victims come to the police only when they experience severe violence?”.…”
Section: Introductionmentioning
confidence: 99%